The potential of organic matter and water management on the alleviation of iron toxicity in rice plants - Nurkholish Nugroho; Budiastuti Kurniasih; Sri Nuryani Hidayah Utami; Wahida Annisa Yusuf (Jurnal Ilmu Pertanian, 2022)
Iron toxicity in rice plants occurs due to the excessive concentrations of ferrous ions (Fe2+) in the soil solution. The application of organic matter and water management is one way to alleviate iron toxicity in rice plants. This study aimed to determine the potential of organic matter and water management in controlling the solubility of Fe2+ in the soil and its effect on the symptoms of toxicity, growth and yield of rice plants. The research was conducted in the greenhouse of the Indonesian Swampland Agricultural Research Institute from August to December 2020, arranged in a completely randomized design with three factors. The first factor consisted of low Fe2+ concentration (<300 ppm, actual acid sulfate soil (AASS)) and high Fe2+ concentration (>300 ppm, potential acid sulfate soil (PASS)), the second factor consisted of waterlogging without leaching and leaching of once every two weeks, and the third factor consisted of without organic matter amendment and with organic matter amendment of 2.5 ton.ha-1. The results showed that the soil leaching in acid sulfate soils decreased the activity of PPO by 10.28% and increased yield by 10.10%. Meanwhile, the application of organic matter in acid sulfate soil decreased the activity of PPO by 8.91% and increased yield by 8.06%. The leaching of once every two weeks and organic matter amendment of 2.5 ton.ha-1 are recommended to alleviate iron toxicity and increase rice productivity in acid sulfate soil.